Psychometric Properties of the Persian Kessler Psychological Distress Scale Among Iranian Older Adults - Elham Lotfalinezhad; Fatemeh Barati; Robab Sahaf; Mohsen Shati; Yadollah Abolfathi Momtaz; Mahshid Forughan; Fatemeh Amini; Devender Bhalla; Shahab Papi; Abolfazl Hosseinnataj (علوم بهداشتی ایران, 2023)
Background and Purpose: We measured the psychometric properties i.e., validity, reliability, and stability of the Persian 10-item Kessler psychological distress scale (K10) among older adults in Iran. Materials and Methods: We recruited elderly (60+ years) subjects (20 per item of the questionnaire) from various sampling units in the general population of Gorgan district, Golestan, Iran. After the translation/back-translation process, the questionnaire underwent various forms of validity and reliability, including Cronbach alpha (overall, by items, and by group of yes to an item and no to an item). The intra-class correlation coefficient was measured at a two-week interval, and inter-rater agreement was also determined. Both exploratory and confirmatory factor analyses were also conducted, along with receiver-operator characteristics vis-à-vis hospital anxiety and depression scale. Results: In total, 190 subjects (47.3% males, mean age: 70.3, 95% CI: 69.2-71.4) participated in the study. A total of 35.8% had psychological distress (PD) (i.e., score >20). The alpha coefficient was 0.88 with no item below 0.86. The alpha coefficients to report a yes to an item (α=0.85) or no to an item (α=0.90) were similar to each other. The intra-class coefficient for test-retest at a two-week interval was 0.90. Exploratory factor analysis showed a one-factor structure of the underlying construct, with a cumulative variance of 97.1%. Confirmatory factor analysis showed high fit indices for the questionnaire (0.91) and a low standardized residual of 0.05. Conclusion: We measured psychometric parameters of the Persian version of the K10 scale for detecting PD among older adults, which was found to be adequately valid, reliable, and stable. Our questionnaire fills the prior gaps regarding the lack of validated tools for the timely detection and management of PD among older adults in the Persian-language cultural contexts. Our study emphasizes that the Kessler questionnaire is a unidimensional scale, and detects non-specific PD with all items indicating a single underlying construct of “distress”.